2009
DOI: 10.1099/mic.0.031153-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Pseudomonas putida CA-3 proteome during growth on styrene under nitrogen-limiting and non-limiting conditions

Abstract: Pseudomonas putida CA-3 is a styrene-degrading bacterium capable of accumulating mediumchain-length polyhydroxyalkanoate (mclPHA) when exposed to limiting concentrations of a nitrogen source in the growth medium. Using shotgun proteomics we analysed global proteome expression in P. putida CA-3 supplied with styrene as the sole carbon and energy source under N-limiting (condition permissive for mclPHA synthesis) and non-limiting (condition non-permissive for mclPHA accumulation) growth conditions in order to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 92 publications
2
33
0
1
Order By: Relevance
“…Nikodinovic-Runic et al . 41 also observed an up-regulation of the biosynthesis of flagella-associated proteins upon exposure of a P. putida to styrene in N starvation conditions. This was attributed to a general stimulation of bacterial motility in response to environmental perturbations like exposure to organic pollutants.…”
Section: Resultsmentioning
confidence: 70%
“…Nikodinovic-Runic et al . 41 also observed an up-regulation of the biosynthesis of flagella-associated proteins upon exposure of a P. putida to styrene in N starvation conditions. This was attributed to a general stimulation of bacterial motility in response to environmental perturbations like exposure to organic pollutants.…”
Section: Resultsmentioning
confidence: 70%
“…qRT-PCR confirmed that four genes were upregulated by more than 10-fold; these were categorized into “amino acid/nucleotide transport and metabolism”. Transcription of BAB_RS24460 was upregulated 39-fold in the mutant strain ∆22915; this is the substrate-binding component of the branched-chain amino acid ABC transporter, responsible for the uptake of leucine, isoleucine and valine [38]; uptake mediated by this transporter contributes to bacterial growth [39], intracellular survival [40], and symbiosis between host and bacteria [41]. The BAB_RS30485 gene, also known as the PotD gene, is the substrate-binding component of the polyamine ABC transporter that preferentially takes up spermidine [42].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is thought that the catalase/peroxidase subfamily provides protection from oxidative stress in bacteria (Nikodinovic-Runic et al 2009). Therefore, the up-regulation of peroxidases in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%